Heterokaryon Formation of Simian Virus 40-transformed Cells in the Presence of Ultraviolet-irradiated Sendai Virus - Dubbs, D. R. (1969)
Most simian virus 40-transformed mouse kidney lines form heterokaryons with CV-1 cells in the presence of ultraviolet-irradiated Sendai. However, two nonyielder lines, mKS-U2 and mKS-U20, fuse poorly.